1995
DOI: 10.1063/1.871178
|View full text |Cite
|
Sign up to set email alerts
|

Modulational and Raman instabilities in the relativistic regime

Abstract: A large amplitude electromagnetic wave propagating in a plasma is known to be subject to severe modulational and Raman instabilities. Previous works were devoted to the weakly relativistic limit and applied mainly to a cold underdense plasma. One extends these works to include the fully relativistic limit for a circularly polarized light for which one derives the dispersion relation in a one-dimensional plasma. The characteristics of the instabilities are also calculated in the case where the plasma is classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(53 citation statements)
references
References 11 publications
2
51
0
Order By: Relevance
“…It was shown that [39][40][41], for a relativistic laser with laser amplitude a > 1 and homogeneous density close to relativistic critical, the nonlinear stage of the instabilities will result in a strong heating of the electron distribution function. The existing analyses are restricted to homogeneous plasmas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was shown that [39][40][41], for a relativistic laser with laser amplitude a > 1 and homogeneous density close to relativistic critical, the nonlinear stage of the instabilities will result in a strong heating of the electron distribution function. The existing analyses are restricted to homogeneous plasmas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Figures 1(b) and 1(c) show the dispersion curves for the relativistic laser amplitudes. At low temperatures, the instability region becomes wider and growth rates become larger at higher laser amplitude and plasma density, in the meanwhile, the instability can develop even when the plasma density is higher than the quarter critical density as clarified before 16,21 . At a 0 = 3 and n e0 = 0.3n c , where…”
Section: A Dispersion Relation Of Srsmentioning
confidence: 99%
“…It was shown that [7][8][9], for the relativistic CP laser radiation with a 0 ≫ 1 and homogeneous density close to relativistic critical, one cannot distinguish these (M and RS) different modes, and the wave numbers of unstable modes have a broad range. While in our case, plasma is inhomogeneous rather strongly, so that if the existing conclusions match our cases need another further study.…”
Section: Envelop Modulation Of Cp Lasermentioning
confidence: 99%